2014
DOI: 10.1007/s00410-014-1034-2
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of mixing and mobilisation in the Bishop Tuff magma body: perspectives from diffusion chronometry

Abstract: Abstract:We present two-feldspar thermometry and diffusion chronometry from sanidine, orthopyroxene and quartz from multiple samples of the Bishop Tuff, California, to constrain the temperature stratification within the pre-eruptive magma body and the timescales of magma mixing prior to its eruption. Two-feldspar thermometry yields estimates that agrees well with previous Fe-Ti oxide thermometry and gives a ~80 °C temperature difference between the earlier-and later-erupted regions of the magma chamber. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(181 citation statements)
references
References 69 publications
6
175
0
Order By: Relevance
“…However, as with the data set presented by Reid et al (2011), Chamberlain et al (2014b do find some systematic relationships between trace elements that they infer to reflect melt evolution and differences between the 'normal Bishop' magma and a late addition of a less-evolved composition (the 'bright-rim' composition). In another paper looking at diffusion of trace elements in quartz, orthopyroxene and sanidine, Chamberlain et al (2014a) concluded that the interaction of the 'normal Bishop' magma with the 'bright-rim' composition occurred over at least 500 years prior to eruption, which they envision to be occurring in a melt-dominated body. Simon et al (2014) combined Nd, Hf and Pb isotopic data, trace-element data, Ar -Ar geochronology, and zircon geochronology for Long Valley rhyolites in a model of magma reservoir evolution over the pre-to post-caldera interval.…”
Section: Crystallization Ages Of Accessory Mineralsmentioning
confidence: 97%
“…However, as with the data set presented by Reid et al (2011), Chamberlain et al (2014b do find some systematic relationships between trace elements that they infer to reflect melt evolution and differences between the 'normal Bishop' magma and a late addition of a less-evolved composition (the 'bright-rim' composition). In another paper looking at diffusion of trace elements in quartz, orthopyroxene and sanidine, Chamberlain et al (2014a) concluded that the interaction of the 'normal Bishop' magma with the 'bright-rim' composition occurred over at least 500 years prior to eruption, which they envision to be occurring in a melt-dominated body. Simon et al (2014) combined Nd, Hf and Pb isotopic data, trace-element data, Ar -Ar geochronology, and zircon geochronology for Long Valley rhyolites in a model of magma reservoir evolution over the pre-to post-caldera interval.…”
Section: Crystallization Ages Of Accessory Mineralsmentioning
confidence: 97%
“…Temperatures are averages from Barker et al (2015) using the orthopyroxene-liquid thermometer of Putirka (2008). Viscocity (log ) of melt (in Pa s ) calculated using the model of Giordano et al (2008) (Allan et al, 2013;Cooper, 2014;Chamberlain et al, 2014), and therefore the zoning observed in BSE images is inferred to be an accurate representation of the Fe-Mg content.…”
Section: References Citedmentioning
confidence: 99%
“…Other studies recognize the importance of alternate initial conditions for diffusion modeling (Costa et al, 2008), including deconvolution of the effects of simultaneous crystal growth and diffusion of Ba and Sr in sanidine (Chamberlain et al, 2014). By employing a third faster diffusing element (Mg), this study reveals that Ba and Sr profiles across the sanidine core-rim boundary reflect changes in melt composition rather than diffusive relaxation across a sharp boundary.…”
Section: Figure 3 Time Scales Between Crystallization and Eruption Cmentioning
confidence: 84%
“…At appropriate degrees of undercooling, experimental crystallization rates (~10 -10 cm/s) predict ~15 yr for growth of the entire sanidine rim (~500 mm) and 1.5-3.5 mo for the growth of the 4-7 mm concentration gradients (see the Data Repository). Any time elapsed between sanidine dissolution in response to rejuvenation and the onset of renewed crystallization must be <~1200 yr due to preservation of 18 O/ 16 O disequilibrium in the resorbed cores of SCL zircons (Bindeman et al, 2008), but is likely much shorter because the entire population of SCL sanidine crystals would be consumed in only ~30-45 yr within heated rhyolite given their rate of dissolution (see the Data Repository). Diffusion during SCL lava emplacement is likely to have been insignificant because silicic lavas are typically emplaced as a series of quickly quenched lobes (e.g., Tuffen et al, 2013).…”
Section: Diffusion Of Elemental Zoning In Sanidinementioning
confidence: 99%